1998
DOI: 10.1007/s000180050251
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental hormones on reproduction

Abstract: Considerable attention has been given in the past few years to the possibility that man-made chemicals (xenobiotics) in the environment may pose a hazard to human reproductive health. The endocrine-disrupting effects of many xenobiotics can be interpreted as interference with the normal regulation of reproductive processes by steroid hormones. Evidence reviewed here indicates that xenobiotics bind to androgen and oestrogen receptors in target tissues, and to androgen-binding protein and to sex hormone-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(53 citation statements)
references
References 200 publications
1
49
0
3
Order By: Relevance
“…Reijnders (1986) has reported a lower E 2 concentration in plasma of common seals fed PCB-contaminated fish than in the control group, and several studies have shown that different PCB congeners and their metabolites may exert both estrogenic and antiestrogenic effects through a wide range of mechanisms (Battershill 1994;Connor et al 1997;Danzo 1998;Dechaud et al 1999;Kester et al 2000;Moore et al 1997;Nesaretnam et al 1996;Wojtowicz et al 2000). In this study, no relationships between E 2 and the investigated factors (age, body mass, capture date, cortisol, ΣPCBs, and PCB-118) were found.…”
Section: Discussionmentioning
confidence: 99%
“…Reijnders (1986) has reported a lower E 2 concentration in plasma of common seals fed PCB-contaminated fish than in the control group, and several studies have shown that different PCB congeners and their metabolites may exert both estrogenic and antiestrogenic effects through a wide range of mechanisms (Battershill 1994;Connor et al 1997;Danzo 1998;Dechaud et al 1999;Kester et al 2000;Moore et al 1997;Nesaretnam et al 1996;Wojtowicz et al 2000). In this study, no relationships between E 2 and the investigated factors (age, body mass, capture date, cortisol, ΣPCBs, and PCB-118) were found.…”
Section: Discussionmentioning
confidence: 99%
“…9 Turning to our analysis of post-retraction citations, we examined the content of articles citing already retracted articles to again assess the reason why articles are citing knowledge acknowledged to be false. Even for the twenty retracted articles in our sub-sample, this is a challenging task because of the Danzo (1998) provides an example of a citation to Arnold that explicitly recognizes the original paper's retraction:…”
Section: Iv5 Content Analysis -Pre-and Post-retraction Citationsmentioning
confidence: 99%
“…OCPs possess a cumulative capacity, slow degradation rate, and their residues are present in the soil, water and sediment even several years after their application (Barlas 1999(Barlas , 2002Singh 2001). OCPs are currently less widely used than these used to be earlier, because of a number of disadvantages including environmental persistence, bioaccumulation and their toxic action upon the reproductive and nervous systems (Danzo 1998;Hellawell 1988;Yamaguchi et al 2003). These compounds may affect the normal function of the endocrine system (Hileman 1994).…”
Section: Introductionmentioning
confidence: 98%